Does financial education matter? Education literacy among undergraduates in Malaysia - Yew, S.Y.; Yong, C.C.; Cheong, K.C.; Tey, N.P. (Faculty of Economics and Administration, University of Malaya, 2017)
Low financial literacy is a global phenomenon. In an increasingly materialistic and complex world, lack of financial literacy can lead to financial problems, even among college and university students. Despite the importance of financial literacy among the young, there is still a dearth of studies on financial literacy and behaviour. Hence, a survey was carried out to provide some insights on this topic. A total of 605 students from four institutions of higher learning in Klang Valley, Malaysia were selected using convenience sampling to provide information on financial literacy, attitude and behaviour as well as financial socialisation factors. The survey revealed that college and university students generally have low financial literacy, a tenuous link between knowledge and attitude but a close association between attitude and behaviour. Parental guidance and life experience were significant predictors of financial knowledge but year of study was not an important predictor. Hence, there is a need to promote experiential learning on financial matters, as financial literacy will lead to positive attitude and good practices.